2017
DOI: 10.1159/000479377
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness Changes in the Pseudoexfoliation Syndrome: A Meta-Analysis of Case-Control Studies

Abstract: Purpose: To evaluate and compare changes in retinal nerve fiber layer (RNFL) thickness in patients with the pseudoexfoliation syndrome (PXS) and healthy controls. Methods: Case-control studies were selected through an electronic search of the Cochrane Controlled Trials Register, PubMed, and Embase. Results were reviewed to ensure that the included studies met prespecified inclusion/exclusion criteria, and the quality of each study was assessed using the Newcastle-Ottawa Scale. All included studies measured ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In the present study, patients with unilateral XFS without glaucomatous optic nerve changes or visual field defects showed thinner RNFL and GCC thicknesses than those of control individuals. Our results were similar to those of previous individual studies and meta-analysis [ 12 , 15 , 18 ]. Our study demonstrated reduced RNFL and GCC thicknesses in superior quadrants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, patients with unilateral XFS without glaucomatous optic nerve changes or visual field defects showed thinner RNFL and GCC thicknesses than those of control individuals. Our results were similar to those of previous individual studies and meta-analysis [ 12 , 15 , 18 ]. Our study demonstrated reduced RNFL and GCC thicknesses in superior quadrants.…”
Section: Discussionsupporting
confidence: 92%
“…Subgroup analysis demonstrated no significant differences in the nasal quadrant regardless of OCT type in their study [ 18 ]. Moreover, publication bias was found in average RNFL thickness and inferior RNFL thickness [ 18 ]. Thus, their results seem similar to our own.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations